Pathophysiology of sepsis: a focus on the activity of interleukin 33 (IL-33) (Research, Society and Development, 2020)
Sepsis is one of the main causes of morbidity and mortality, its prognosis is related to every pathophysiological process that occurs during the condition. In this context, this research aims to present the performance of Interleukin 33 (IL-33) in the pathophysiological process that occurs in sepsis and evaluate its involvement in immunosuppression, since studies show that IL-33 in the action of the inflammatory process triggers T-type responses help 2 (Th2), in addition to being a kind of alarmin for several cells Of patients who pass through sepsis. This research is an integrative literature review, based on articles published from 2015 in Portuguese, English arranged in the LILACS and MEDLINE databases. As a result, 24 studies were selected where 15 of these composed two categories: functional activity of IL-33 in the case of patients in sepsis, and Immunosuppression due to IL-33 activity in a patient after recovery from the sepsis process. Thus, it was concluded that this cytokine acts as a path of several trails, where it benefits the body, also bringing harm in certain triggers associated with other processes. Understanding these mechanisms is extremely relevant to assist in the development of effective diagnosis and therapies to minimize subsequent damage caused by sepsis.